Higher Drop in Speed during a Repeated Sprint Test in Soccer Players Reporting Former Hamstring Strain Injury - Røksund, Ola D.; Kristoffersen, Morten; Bogen, Bård E.; Wisnes, Alexander; Engeseth, Merete S.; Nilsen, Ann-Kristin; Iversen, Vegard V.; Mæland, Silje; Gundersen, Hilde (Frontiers in Physiology, 2017)
Aim: Hamstring strain injury is common in soccer. The aim of this study was to evaluate the physical capacity of players who have and have not suffered from hamstring strain injury in a sample of semi-professional and professional Norwegian soccer players in order to evaluate characteristics and to identify possible indications of insufficient rehabilitation. Method: Seventy-five semi-professional and professional soccer players (19 ±3 years) playing at the second and third level in the Norwegian league participated in the study. All players answered a questionnaire, including one question about hamstring strain injury (yes/no) during the previous two years. They also performed a 40m maximal sprint test, a repeated sprint test (8 x 20m), a countermovement jump, a maximal oxygen consumption (VO2max) test, strength tests and flexibility tests. Independent sample t-tests were used to evaluate differences in the physical capacity of the players who had suffered from hamstring strain injury and those who had not. Mixed between-within subject’s analyses of variance was used to compare changes in speed during the repeated sprint test between groups. Results: Players who reported hamstring strain injury during the previous two years (16%) had a significantly higher drop in speed (0.07 vs. 0.02 seconds, p=0.007) during the repeated sprint test, compared to players reporting no previous hamstring strain injury. In addition, there was a significant interaction (groups x time) (F=3.22, p=0.002), showing that speed in the two groups changed differently during the repeated sprint test. There were no significant differences in relations to age, weight, height, body fat, linear speed, countermovement jump height, leg strength, VO2max or hamstring flexibility between the groups. Conclusion: Soccer players who reported hamstring strain injury during the previous two years showed significant higher drop in speed during the repeated sprint test compared to players with no hamstring strain injury. The maximal speed, leg strength, ability to produce maximal power, endurance capacity and hamstring flexibility was similar for both groups. Thus, a repeated sprint test consisting of 8 x 20m could be used as a field-based diagnostic tool to identify players in need of reconditioning programs to ensure complete post-injury rehabilitation.